Report of the Coal Washeries Committee 1954 - Planning Commission (Planning Commission, 1954)
Of the 36 million tons or so of coal raised at present in India, barely 30% is of "selected grade” qualities, having heating values of 12500 B.t.u. (as received) or above. Between the two great wars, however, the major part of the production of coal came from the Upper Seams of the Jharia coalfield and a few of the well-known Seams (e.g. Dishergarh, Poniati etc.) of the Raniganj coalfield which produce coal of good quality (less than 13% ash). Between the two wars also, a large part of the country's reserves of good quality coal (particularly coking coal) was seriously depleted due to concentrated production from these sources, by bad or indifferent mining and large losses due to fires and flooding.
India Coal Board
India Coal Board